Unhealthy Diet and Stress are Correlated with Premenstrual Syndrome in Adolescent Girls in Tangerang - Huwaida, Dhea Zahra; Dewi, Yulia Lanti Retno; Kusnandar, Kusnandar (Media Gizi Indonesia, 2022)
Adolescent girls is one of the age groups that are vulnerable to menstrual disorders, especially in the first year after menarche. Premenstrual syndrome (PMS) is a group of physical and emotional symptoms that emerge 7 to 14 days before menstruation and diminish once menstruation starts. This study was aimed to analyze the correlation between unhealthy diets and stress on premenstrual syndrome in adolescent girls. This study employed an observational study with a cross-sectional approach. The population of this study was all adolescent girls at State Junior High Schools in Tangerang City who aged 13-15 years. The sampling technique used cluster random sampling, consisting of 120 respondents. The data was collected through validated questionnaires, namely Food Frequency Questionnaire (FFQ), Perceived Stress Scale (PSS-10), and Shortened Premenstrual Assessment Form (SPAF). The obtained data were analyzed using Spearman statistical test. The results showed that there was a significant correlation between sweet foods (p = 0.039; r = 0.188), sweet drinks (p = 0.006; r = 0.247), salty foods (p = 0.026; r = 0.203), fatty foods (p = 0.000; r = 0.366) and fast food (p = 0.001; r = 0.313) and stress (p = 0.000; r = 0.564) on PMS. In conclusion, maintaining healthy diet and controlling stress is important to prevent and manage PMS among female adolescent.